Money and markets: a monetarist view - Sprinkel, Beryl W. (Homewood, Ill., Richard D. Irwin, 1971)
The book explain the increasingly popular monetarist theory of aggregate demand and to relate changes in money to such important economic variables as business cycles, inflations, economic growth, and stock and bond prices.
Includes index
Includes bibliographical references.
usc 31/8/17
Loans
Keywords: Money; Business cycles; Economic conditions